Role of calcium and mechanical damage in the development of localised premature softening in coolstored kiwifruit : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Science at Massey University - Davie, Ivan John (Massey University, 1997)
Preharvest, harvest, and postharvest factor(s) were examined to identify the causes of premature quality loss during long term coolstorage of kiwifruit (Actinidia deliciosa). Investigation centred around the role of mechanical damage and calcium in the development of softening disorders, including soft patches (localised soft areas on fruit surface), premature softening, and low temperature breakdown (LTB) during storage. Kiwifruit were vulnerable to compression and impact from harvest onwards, with damage usually being expressed after a period of coolstorage. Physical damage normally just affected the fruit tissue in direct contact with the applied force. Impact damage, and to a lesser extent compression damage, depended on the size of the force and firmness of fruit when damaged. As kiwifruit softened, their susceptibility to soft patch development as a result of physical damage increased whereas the likelihood of flesh fracture in response to impact declined. These changes are attributed to the change in nature of the flesh, which is 'brittle' at harvest and 'viscoelastic' after softening. Physical damage to coolstored kiwifruit caused a slight drop in final firmness whereas there was no effect on firmness if it occurred at harvest. Fruit with softening disorders consistently had lower calcium contents (about 12% less) than equivalent healthy fruit. Fruit with soft patches had a high phosphate content, low dry matter, and at harvest, a low soluble solids content. A causative role for calcium in soft patch development was demonstrated by preharvest calcium treatments that elevated calcium content of the harvested fruit. Other orchard factor(s) were probably the cause of a weaker relationship between calcium content at harvest and storage behaviour of fruit. Although firmness at harvest declined with later picking, after coolstorage, fruit harvested more mature had a higher firmness and lower incidence of LTB. Symptoms for LTB were consistent with chilling injury whereas soft patches appeared to be due to localised premature senescence and not low temperature. A conceptual model of key factor(s) which cause the initiation and development of softening disorders in kiwifruit is proposed. Implications of this model for further investigation of these phenomena and for commercial handling of fruit are discussed. Further development of this model to produce a predictive model of fruit storage potential would require further characterisation of other important influences in storage behaviour
Keywords: Kiwifruit; Storage; Postharvest; Coolstores; New Zealand; Kiwifruit quality